Selective Detection of Ethylene Gas Using Carbon Nanotube-based Devices: Utility in Determination of Fruit Ripeness - Esser, Birgit; Schnorr, Jan M.; Swager, Timothy M. (Angewandte Chemie International Edition, 2012)
Comparing apples and oranges: A chemoresistive sensor for ethylene can be obtained simply by mixing copper complex 1 with single‐walled carbon nanotubes. The resulting devices show sub‐ppm sensitivity and high selectivity towards ethylene. The utility of the sensor was demonstrated by following ripening stages in different fruits.